Amphetamine-induced cardiomyopathy complicated by embolic stroke: a case report. Issue 2 (9th February 2022) - Chapman, Lucy; Tahir, Ismail; Sheriff, Neha; Colwell, Niall
Abstract: Background: Amphetamine use causes cardiomyopathy via catecholamine-mediated effects such as tachycardia, hypertension, vasoconstriction, and direct cardio-toxic effects. Traditionally, an increased risk of haemorrhagic stroke is associated with amphetamine use. However, up to one-third of stimulant-associated cardiomyopathy patients have left ventricular (LV) thrombus formation leading to an increased risk of systemic embolization. We report a case of amphetamine-induced cardiomyopathy complicated by embolic stroke secondary to LV thrombus. Case summary: A 38-year-old man with 6-month history of sustained amphetamine use presented to the emergency department with left-sided weakness, facial droop, and dysarthria. Angiography confirmed right middle cerebral artery thrombus. Prompt mechanical thrombectomy yielded full neurological recovery. Dyspnoea prompted transthoracic echocardiography showing dilated cardiomyopathy with an ejection fraction of 5% and LV thrombus. Anticoagulation was initiated with warfarin as well as pharmacological therapy for heart failure with reduced ejection fraction including bisoprolol, spironolactone, loop diuretic, and sacubitril/valsartan. He was discharged successfully following resolution of ventricular thrombus and medical management of heart failure. Clinical recovery was hampered by psychosocial factors resulting in non-adherence to medical therapy and continued amphetamine use. Conclusion: Sustained amphetamine use can result in severe dilated cardiomyopathy with LV thrombus formation and embolic complications such as ischaemic stroke. Avoidance of amphetamines in conjunction with guideline-directed pharmacological management are key components of therapy. However, psychosocial factors can exert significant influence on recovery.